Regression Analysis for the Adsorption Isotherms of Betacyanin Extracts from the Dragon Fruit Peel onto the Spun Silk Yarn - Norasiha, Hamid; Mimi Sakinah, A. M.; Mazrul Nizam, Abu Seman (Penerbit Universiti Malaysia Pahang, 2016)
The betacyanin pigment extracted from the dragon fruit peel has a potential to be a natural dye as an alternative to replace the synthetic dyes. To investigate the dyeability of spun silk with betacyanin pigment, the adsorption isotherm models were performed. The equilibrium adsorption data were analyzed using the Langmuir, Freundlich, and Temkin isotherm models. In order to determine the best-fit isotherm for each system, three error analysis methods were used to evaluate the data, namely the sum of the squares of the errors, residual root mean square error and chi-square test. On the basis of low three error analysis and high correlation of determination, it was found that the Langmuir isotherm model fitted well with the experimental data. Therefore, it can be concluded that the adsorption process of betacyanin pigment onto the spun silk followed the Langmuir isotherm model. Moreover, the adsorption features of the experimental system might be caused by the monolayer adsorption.